2008
DOI: 10.1016/j.neuroimage.2007.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear neurobiological probability weighting functions for aversive outcomes

Abstract: While mainstream economic models assume that individuals treat probabilities objectively, many people tend to overestimate the likelihood of improbable events and underestimate the likelihood of probable events. However, a biological account for why probabilities would be treated this way does not yet exist. While undergoing fMRI, we presented individuals with a series of lotteries, defined by the voltage of an impending cutaneous electric shock and the probability with which the shock would be received. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 47 publications
(44 reference statements)
12
65
0
Order By: Relevance
“…The cost of computing values provides a normative rationale for why valuation may be done in the absence of free choice. Figure 1, adapted from (Berns, Capra et al 2007) provides strong evidence that valuation is performed even in imperative trials, and in a way that is relevant for free-choice trials. It shows how well a valuation model fit to neuronal activation during imperative trials can predict choice in free-choice trials.…”
Section: Distinguishing Valuation and Choicementioning
confidence: 88%
See 1 more Smart Citation
“…The cost of computing values provides a normative rationale for why valuation may be done in the absence of free choice. Figure 1, adapted from (Berns, Capra et al 2007) provides strong evidence that valuation is performed even in imperative trials, and in a way that is relevant for free-choice trials. It shows how well a valuation model fit to neuronal activation during imperative trials can predict choice in free-choice trials.…”
Section: Distinguishing Valuation and Choicementioning
confidence: 88%
“…Neural activation identified in imperative trials (the fMRI model) predicts choices better than actual choice in free-choice trials when the two available options are close in ranking. Source: (Berns, Capra et al 2007). Figure 3 Caption: Average firing rates of a cluster of caudate neurons in the monkey brain that encode the value of eye movements (saccades) in the preferred direction.…”
Section: Figurementioning
confidence: 99%
“…The general framework and voltage setting procedure were similar to the experiment described in Section 2, except that the shocks were delivered probabilistically and all shocks occurred with the same delay. The study is reported in more detail in Berns et al (2007) and in Berns et al (2008).…”
Section: Probability Weightingmentioning
confidence: 96%
“…The second study, presented in Section 3 and also reported in Berns et al, (2007Berns et al, ( , 2008, concerns probability weighting. This is the notion that individuals make decisions as if they transform probabilities by a function π(p), where p is the probability of an event.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation